A Scoping Review of Burnout Among Nurses: Causes, Consequences and Interventions - Aeshah Abdu Ahmed Hadadi, Fatimah Hassan Al Abbas, Afnan Ali Ahmed Almusharraf, Layla Hassan Ghanem Alghanem (International Journal of Scientific Research and Innovative Studies, 2024)
Nurse burnout is an ongoing threatening problem to the healthcare system across the world, particularly after the COVID-19 pandemic. Being defined in terms of exhaustion, deprivation of humanity, and a lower degree of personal accomplishment, nurse burnout does not only impact personal well-being but also risks the life and well-being of patients, the quality of care, and the sustainability of healthcare workforce. The purpose of the proposed scoping review is to synthesize recent academic literature (202024) on multifactorial conditions of nurse burnout, various outcomes of burnout, and the variety of interventions adopted to alleviate the problem of burnout. According to PRISMA-ScR and the framework mentioned by Arksey and OMalley, more than 45 empirical studies, systematic reviews, and meta-analyses were reviewed. Among the most important contributing factors, findings show workload intensity, emotional strain, organizational climate, and the absence of institutional support. The outcomes are reduced job chances, escalated mistakes in clinical experiences, and turnover. There are the following promising interventions to deal with intimate partner violence: mindfulness-based interventions, electronic support tools, resilience training, and organizational reform. Based on this review, nurse burnout is recommended to be dealt with on multi-level, both individual and structural. Keywords: Burnout in nurses; emotional burnout; resilience; critical workforce; scoping review; an intervention; organizational support; COVID-19; human mind; nursing administration. Received Date: February 25, 2024 Accepted Date: March 12, 2024 Published Date: April 17, 2024 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/392 https://doi.org/10.5281/zenodo.15798184